Transmembrane adaptor protein PAG is a mediator of PD-1 inhibitory signaling in human T cells - Marianne Strazza (Nature Portfolio, 2021)
Strazza et al. show that phosphoprotein associated with glycosphingolipidenriched microdomains 1 (PAG) is phosphorylated following PD-1 ligation. They find that PAG deletion sensitizes tumors to PD-1 blockade. This study suggests PAG as a critical mediator of PD-1 signaling and a promising target to enhance T cell activation in tumors.